Procedure for the Isolation of Endothelial Cells from Human Cerebral Arteriovenous Malformation (cAVM) Tissues - Hao, Qiang; Chen, Xiao-Lin; Ma, Li; Wang, Tong-Tong; Hu, Yue; Zhao, Yuan-Li (Frontiers in Cellular Neuroscience, 2018)
In this study, we successfully established a stable method for the isolation of endothelial cells (ECs) from human cerebral arteriovenous malformation (cAVM) tissues. Despite human cAVM tissues having a minor population of ECs, they play an important role in the manifestation and development of cAVM as well as playing a role in hemorrhagic stroke and thrombogenesis. To characterize and understand the biology of ECs in human cAVM (cAVM-ECs), methods for the isolation and purification of these cells are necessary. We have developed this method to reliably obtain pure populations of ECs from cAVMs. To obtain pure cell populations, cAVM tissues were mechanically and enzymatically digested and the resulting single cAVM-ECs suspensions were then labeled with antibodies of specific cell antigens and selected by flow cytometry. Purified ECs were detected using specific makers of ECs by immunostaining and used to study different cellular mechanisms. Compared to the different methods of isolation ECs from tissues, we could isolate ECs from cAVMs confidently, and the numbers of cAVM-ECs harvested were almost similar to the amounts present in vessel components. In addition to optimizing the protocol for isolation of ECs from human cAVM tissues, the protocol could also be applied to isolate ECs from other human neurovascular diseased tissues. Depending on the tissues, the whole procedure could be completed in about 20 days.